Susan Isaacs A Life Freeing the Minds of Children - Graham, Philip (Open Book Publishers, 2023)
This revised and expanded edition of Susan Isaacs: A Life Freeing the Minds of Children by Philip Graham, provides a comprehensive biography of a highly influential educationist and psychoanalyst. The book covers Isaacs' childhood through to the end of her life, making it of great interest to historians of British education and of psychoanalysis as well as to practicing early years teachers and psychoanalysts. Graham describes the origins of the theories behind Isaacs' work while also placing her contribution into context with other contemporary educationists. He draws on a range of sources including her own published and unpublished papers, multiple archives and intimate letters. Such wealth of information and anecdotes gives an insight into her childhood, marriage, and career creating a deeper understanding of both Isaacs' personal life and her achievements. As only the second biography on Isaacs, this book is a valuable resource that shines a light on the life of a figure who has often been neglected in this field of study. It provides a shift away from the various male-dominated accounts currently prevalent within this area of research. Susan Isaacs is crucial reading to raise our awareness and appreciation of the person behind the work, while also highlighting and celebrating the impact she has made on today's education and psychoanalytic practice.